The effect of temperature on the leaching of monazite obtained from heavy mineral sands - Shin, H.; Park, H.; Yoo, Kyoungkeun (Taylor & Francis, 2012)
Pressure leaching, electrogenerated chlorine leaching and concentrated sulfuric acid leaching were performed to investigate the leaching behavior of monazite concentrate with various temperature ranges. The pressure leaching was tested at 5 atm and 220°C and the concentrations of Ce and La increase with increasing sulfuric acid concentration from 0.01 mol/L to 1 mol/L and decreasing the particle size of monazite concentrate from -200 mesh - + 325 mesh to -325 mesh. In the electrogenerated chlorine leaching system, the concentration of La decreases with increasing temperature from 30°C to 70°C, which resulted from a decrease in solubility of chlorine with increasing temperature. In the concentrated sulfuric acid leaching system, the leaching ratios of La and Nd increase to over 99% with increasing temperature to 220°C. The higher metal concentration of Ce, La and Nd are obtained in the concentrated sulfuric acid leaching system than in the pressure leaching and the electrogenerated chlorine leaching system. This result suggests that higher temperature and concentration of sulfuric acid could accelerate the dissolution of monazite concentrate.